C‐THV measures of self‐expandable valve positioning and correlation with implant outcomes. Issue 6 (17th July 2014) - Codner, Pablo; Lavi, Ifat; Malki, Guy; Vaknin‐Assa, Hana; Assali, Abid; Kornowski, Ran
<x xml:space="preserve">Abstract</x> Background Accurate positioning of the valve device during transcutaneous aortic valve implantation (TAVI) is of crucial importance. The Paieon C‐THV navigation system has been designed to correctly guide device deployment during TAVI. Objectives Using this navigation system we aimed to determine the correlation between the anatomic measures of the native aortic valve and the deployed self‐expandable valve positioning and to explore the impact upon procedural outcomes. Methods We analyzed data of 68 patients with severe symptomatic aortic stenosis undergoing TAVI, using the catheter‐based Medtronic‐CoreValve self‐expandable system. Patients were subdivided into two groups according to whether the C‐THV system was used (50) or not (18) during the implantation process. Analysis of geometrical outcomes vs. clinical outcomes including postprocedural electrical conduction defect and/or para‐valvular leaks was performed. Results Taking the target implantation line as a reference; relatively lower vs. higher implantations correlated with a higher frequency of any new onset electrical conduction defect (ECD). The mean corresponding distance from valve inferior edge below the virtual aortic annulus line was 3.0 ± 1.6 mm vs. 1.2 ± 1.3 mm in patients with (38.5%) vs. without any new onset ECD, respectively (P = 0.05). The use of C‐THV navigation seemed to correlate with higher valve implants but it had no impact on the occurrence of postprocedural paravalvular leaks. Conclusions Self‐expandable valve implants guided by C‐THV navigation seems to be associated with more precise implants and lower risk for postprocedural electrical conduction defects, due to higher location in relation to the target line. © 2014 Wiley Periodicals, Inc.